Turn Continuations and Gesture: “And Then”-Prefacing in Multi-Party Conversations - Rönnqvist, Sara; Lindström, Jan (Frontiers in Communication, 2021)
This article offers an analysis of turn-expanding practices with the connective å sen ‘and then’ in Swedish multi-party conversations in which the participants discuss and assess works of visual art. The connective is recurrently used to introduce a turn continuation, i.e. a stretch of talk that is produced after a possibly completed turn-constructional unit (TCU). We identity three types of continuations: same-speaker continuations, occurring post gap or post-other talk, and other-continuations by the next speaker. Some of the “and then”-continuations are clausal, syntactically free-standing, while non-clausal continuations have more in common with TCU-increments. “And then”-continuations specify, restrict or redirect the unfolding contribution while at the same time orienting to a collective interactional project. In same-speaker continuations, the speaker can introduce a new aspect of the established theme or offer an account. Other-continuations can be used to achieve a shift in footing to introduce a contribution of more personal interest. Both grammar and embodied resources (especially hand gestures) are activated in the management of the completion of a prior turn-unit, the initiation of a turn continuation and the re-completion of the speaker’s turn. The typical multimodal trajectory is: syntactic completion of a first unit/retracted gesture, link to prior talk and upcoming talk with “and then” followed by the core of the continuation/a re-deployed gesture, and finally, syntactic completion of the continuing unit/retracted gesture to a rest position.